The Anti-Tumor Efficacy of Verbascoside on Ovarian Cancer via Facilitating CCN1-AKT/NF-κB Pathway-Mediated M1 Macrophage Polarization - Ren, Yu; He, Jinying; Zhao, Wenhua; Ma, Yuzhen (Frontiers in Oncology, 2022)
Background: Ovarian cancer (OC) is the leading cause of gynecological cancer-related mortality. Verbascoside (VB) is a phenylpropanoid glycoside from Chinese herbs, with anti-tumour activities. This study aimed to investigate the effects and mechanism of VB on OC. Methods: OC cell lines SKOV3 and A2780 were used in this study. Cell viability, proliferation, and migration were measured using CCK-8, clonogenic, and transwell assays, respectively. Apoptosis and M1/M2 macrophages were detected using flow cytometry. The interaction between VB and CCN1 was predicted by molecular docking. The mRNA expression of CCN1 was detected by RT-qPCR. The protein levels of CCN1, AKT, p-AKT, p65, and p-p65 were determined by western blotting. A xenograft mice model was established for in vivo validation. Results: VB inhibited OC cell proliferation and migration in a dose-dependent manner, and promoted apoptosis and M1 macrophage polarisation. VB downregulated CCN1 and inhibited the AKT/NF-κB pathway. LY294002, an AKT inhibitor, potentiated the anti-tumour effects of VB. CCN1 overexpression weakened the anti-tumour effects of VB and VB + LY294002. In vivo experiments verified that VB inhibited tumour growth and promoted M1 polarisation, which is regulated by the CCN1-mediated AKT/NF-κB pathway. Conclusion: VB triggers the CCN1-AKT/NF-κB pathway-mediated M1 macrophage polarization for protecting against OC.